Al-Madd Wa al-Qashr : Pengaruhnya Terhadap Makna Ayat al-Qur’ân - Muhammad Rizqi (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2014)
This article discusses about al-madd wa al-qashr and it’s influence on the meanings of al-Quran verses. Mad and Qashar is regarded as an important topic in the study of tajwid because it may change the meaning and the content of al-Quran verses when there is a mistake in applying it. Therefore, this topic is also discussed in the study of ulum al-Quran. Several forms of mistake in applying Mad and Qashar when someones reads al-Quran, can be described as follows; the mistake defecting the content of al-Quran, mistake not defecting the content of al-Quran but changing the meaning, mad and qashar stimulating polemic among ulamas, and mad and qashar which do not ruin the meaning but breaks tadjwid rules.